Implementation of Home Affairs Ministerial Regulation No. 11 of 2023 Concerning Facilities and Infrastructure for Community Protection Task Forces and Community Protection Units in the Perspective of Siyasah Dusturiyah (Case Study in Perbarakan Village, Pagar Merbau District, Deli Serdang Regency) - Tarigan, Fadhlan Fahmi; Suparmin, Sudirman (LEGAL BRIEF, 2025)
This article discusses the implementation of Ministry of Home Affairs Regulation (Permendagri) No. 11 of 2023 concerning Facilities and Infrastructure for the Community Protection Task Force (Satgas Linmas) and the Community Protection Unit (Satlinmas) in Perbarakan Village, Pagar Merbau District, Deli Serdang Regency. This study aims to understand how the regulation is implemented in maintaining village security and the role of Satlinmas as the front line in maintaining order and safety in the village environment. The research uses an empirical juridical method. The findings indicate that the implementation of Permendagri No. 11 of 2023 in Perbarakan Village has not been optimal due to the absence of a formally established Satlinmas unit. This has resulted in a weak security system in Perbarakan Village. From the perspective of siyasah dusturiyah, maintaining security is a mandate of leadership that must be carried out for the public good. Therefore, active community participation is a key element in building an inclusive and sustainable village security system